Loss‐of‐function KCNH2 mutation in a family with long QT syndrome, epilepsy, and sudden death. Issue 8 (30th July 2013) - Partemi, Sara; Cestèle, Sandrine; Pezzella, Marianna; Campuzano, Oscar; Paravidino, Roberta; Pascali, Vincenzo L.; Zara, Federico; Tassinari, Carlo Alberto; Striano, Salvatore; Oliva, Antonio; Brugada, Ramon; Mantegazza, Massimo; et al.
Summary There has been increased interest in a possible association between epilepsy channelopathies and cardiac arrhythmias, such as long QT syndrome (LQTS). We report a kindred that features LQTS, idiopathic epilepsy, and increased risk of sudden death. Genetic study showed a previously unreported heterozygous point mutation (c.246T>C) in the KCNH2 gene. Functional studies showed that the mutation induces severe loss of function. This observation provides further evidence for a possible link between idiopathic epilepsy and LQTS.